Estimation of Adult Mortality from Widowhood Information (The Pakistan Development Review, 1977)
Most of the developing countries of the third world, either have an inadequate or virtually no vital registration system. The data collected from the population censuses in these countries are defective. In this situation it is hardly possible to measure mortality directly. So demographers have tried to develop indirect methods in order to overcome this problem. A widely known indirect method of estimating adult mortality is the Orphan hood method developed by Brass and Hill [5]. The method has been applied to a wide range of the populations in the developing regions particularly several African and Latin American countries, and has been found to yield a reasonable level of adult mortality.